Pandangan Masyarakat tentang Keulamaan Perempuan - Napilah, Paridah; Kuswana, Dadang; Qomaruzzaman, Bambang (Program Studi Studi Agama-Agama Pascasarjana UIN Sunan Gunung Djati Bandung, 2021)
This research started from the differences in the people's views in Sagaranten District, Sukabumi Regency related to female clerics. It stems from the idea that it is appropriate for the ulama to be addressed to men with religious knowledge because the ulama are heirs to the prophets while the prophets are men. In addition, women are a place for slander so they have strict limits when working in society. The author uses descriptive qualitative methods with data collection techniques through observation, in-depth interviews, and documentation. The results of this study indicate that the people of Sagaranten District, Sukabumi Regency have both traditional and modern patterns of thought. The conventional view sees that a woman who has religious knowledge cannot carry out religious activities in a community with a mixed congregation of men and women. It is based on women being slander so that a woman's voice is considered aurat (which must be hidden). Second, the modern view views that women who have religious knowledge can be involved in society. There are no restrictions as long as they are able and have the opportunity.